MODERN THEORIES OF LEADERSHIP IN THE EDUCATIONAL INDUSTRY - Gribovych , A. L. (The actual problems of regional economy development, 2018)
In the conditions of information society, in addition to information, human capita is important. Therefore, on the development of the modern economy the efficiency of the educational sector is influenced. As a result, higher requirements are put forward especially for higher education its effective organization and management. In the management of human resources, an institution of leadership plays an important role. For this aim, modern transformations of leadership theories are systematized. Their projection on the educational branch is performed. The classification of leaders in higher education institutions is proposed.